FAKTOR RISIKO KEJADIAN COVID-19 PADA PENDERITA HIPERTENSI DI KECAMATAN TAPOS, KOTA DEPOK 2021 - Hana Theresia Barus (2022)
The Covid-19 incident has spread to foreign countries and has been declared as pandemic. One of the factors that caused the high incidence of cases and deaths due to Covid-19 is comorbid. Hypertension is the main comorbid of Covid-19. This study aims to analyze the risk factors for Covid-19 in patients with hypertension at Tapos District, Depok City. This research used a cross-sectional study design. The sample in this study was 100 people who were taken using simple random sampling technique. The analysis used Chi-Square and multiple logistic regression. The results of bivariate analysis showed that age had a significant relationship with the incidence of Covid-19 (p value = 0.019). The results of multivariate analysis showed that age was the most influential factor in the incidence of Covid-19 with POR = 3.7 (95% CI = 1.3-10.4) after adjusted with gender, education, occupation, and limiting mobilization. This study concludes that people with hypertension aged 51 years or more are at risk of contracting Covid-19. Suggestions that can be given are to be more disciplined in implementing 5M health protocol, especially limiting mobilization by reducing the frequency of visiting public places when the activities are not too important, and implementing healthy lifestyle also consuming healthy food.